Design and Synthesis of New Mefenamic Acid Derivatives as Anti-Inflammatory Agents - Abdul-Razzak, Nadeem A (Al-Nahrain Journal of Science, 2018)
This study includes design and synthesis of new non-steroidal anti inflammatory agents (NSAIDs) with expected cyclooxygenase-2 (COX-2) selective inhibition to achieve better activity and low gastric side effects. Two mefenamic acid derivatives were designed and synthesized as potential NSAIDs. In vivo acute anti-inflammatory effect of the synthesized agents (compound 2and 3) was evaluated in the rat using egg-white induced paw edema model of inflammation. Preliminary pharmacological study revealed that compound 2and 3 produced a significant reduction in paw edema with respect to the effect of propylene glycol 50% v/v (control group), moreover compound 2 exhibited comparable anti-inflammatory effect to that of aspirin after 120 and 210 minutes and compound 3 has less anti-inflammatory effect, which encourages the continuation of the search to identify their selectivity toward COX-2 isoenzymes.